2017
DOI: 10.1212/wnl.0000000000003919
|View full text |Cite
|
Sign up to set email alerts
|

Body composition status and the risk of migraine

Abstract: Objective: To evaluate the association between migraine and body composition status as estimated based on body mass index and WHO physical status categories.Methods: Systematic electronic database searches were conducted for relevant studies. Two independent reviewers performed data extraction and quality appraisal. Odds ratios (OR) and confidence intervals (CI) were pooled using a random effects model. Significant values, weighted effect sizes, and tests of homogeneity of variance were calculated.Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 39 publications
4
73
0
Order By: Relevance
“…Animal studies showed that obesity reduced gut permeability, reduced expression of tight junctions and could influence intestinal microbiota composition [140]. Pieces of evidence showed that obesity could increase the risk of episodic and chronic migraine [54,141] while weight reduction can decrease the intensity, frequency, and duration of migraine headache in adults [142][143][144] and adolescents [145]. The link between obesity and headache was proposed to be attributed to shared pathophysiological features.…”
Section: Weight Loss Approaches In Migraine/headachementioning
confidence: 99%
“…Animal studies showed that obesity reduced gut permeability, reduced expression of tight junctions and could influence intestinal microbiota composition [140]. Pieces of evidence showed that obesity could increase the risk of episodic and chronic migraine [54,141] while weight reduction can decrease the intensity, frequency, and duration of migraine headache in adults [142][143][144] and adolescents [145]. The link between obesity and headache was proposed to be attributed to shared pathophysiological features.…”
Section: Weight Loss Approaches In Migraine/headachementioning
confidence: 99%
“…A more recent meta-analysis of 12 studies indicated that both obesity (BMI ≥30) and underweight (BMI <18.5) were associated with the risk of migraine. 33 There are a number of additional limitations. It should be noted that we relied on self-reported medical diagnosis of comorbidities and concomitant conditions, which could lead to either underascertainment or overascertainment of specific comorbidities.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…[32][33][34][35][36] Migraine symptoms improved in most studies after weight loss in overweight and obese patients, by bariatric surgery [37][38][39][40][41] or lifestyle changes (including diet) in adults 39,41 and adolescents. [32][33][34][35][36] Migraine symptoms improved in most studies after weight loss in overweight and obese patients, by bariatric surgery [37][38][39][40][41] or lifestyle changes (including diet) in adults 39,41 and adolescents.…”
Section: Evaluating Dietary Recommendations For Migraine In Light Of mentioning
confidence: 99%
“…Maintain a Healthy Weight.-Obesity is associated with both a higher prevalence of migraine disease and a higher risk of progression from episodic to chronic migraine. [32][33][34][35][36] Migraine symptoms improved in most studies after weight loss in overweight and obese patients, by bariatric surgery [37][38][39][40][41] or lifestyle changes (including diet) in adults 39,41 and adolescents. 42,43 Specific mechanisms connecting weight loss with migraine improvement have yet to be elucidated.…”
Section: Favorable Risk: Benefit Analysis-omega-3:omega-6mentioning
confidence: 99%